Current status of carotid endarterectomy and stenting for symptomatic carotid stenosis. - Rothwell, P (2007)
There is still considerable uncertainty about the place of carotid stenting in patients with recently symptomatic carotid bifurcation stenosis. Most reviews of carotid endarterectomy versus carotid stenting concentrate on technical aspects and advances in stenting, but the techniques involved in both carotid endarterectomy and stenting are evolving. In addition to reviewing the results of the various randomised controlled trials of carotid endarterectomy versus stenting for symptomatic carotid stenosis, this review considers recent advances and current best practice for endarterectomy. Ongoing randomized trials will determine whether or not the procedural risk of stroke and death is definitely lower with endarterectomy than with stenting, but the key issue that remains to be determined reliably is how the procedural risks of stenting vary with patient characteristics - perhaps the most important question being not whether endarterectomy is better than stenting or vice versa, but for whom is one technique likely to be better than the other.